Intermolecular interactions between milk proteins and molecules of interest in the food area - Lelis, Carini Aparecida (2019)
Milk proteins have been studied for the transport of small molecules, such as pharmaceuticals, bioactive compounds, dyes, etc. These proteins have in their structure sites capable of interacting with hydrophobic compounds and thus carry them. The objective of this study was to study the molecular mechanisms involved in the interaction between curcumin (CUR) (bioactive compound) and lactoferrin (bLF) and enrofloxacin (ENRO) and bovine serum albumin (antibiotic used in the treatment of cows with mastitis) under different temperature conditions and at physiological pH. For the interaction study between bLF and CUR, sensitive and efficient techniques were used, such as fluorescence and surface plasmon resonance (SPR). Fluorescence results showed that the fluorescence intensity of bLF decreased with increasing concentrations of CUR. The fluorescence quenching mechanism was classified as static, showing the occurrence of complex formation between bLF and CUR under the thermodynamic conditions studied. In addition, the Gibbs free energy variation of the complexation was negative, being governed by entropy. SPR analysis also demonstrated the occurrence of complex formation between bLF and CUR. However, at low temperatures (285.15 K to 293.15 K) the process was governed by entropy, and at higher temperatures (297.15 K at 301.15 K) was governed by enthalpy. In addition, it was found that the complex formed had lower energy transfer capacity in the potential forms than the free molecules. The kinetic study of complex formation between bLF and CUR showed that the activation energy for association and dissociation of the complex (bLF-CUR) increased with increasing temperature. At low temperatures, the CUR showed to interact preferentially on the surface of the bLF, already at higher temperatures, the CUR penetrates inside the protein. It was also verified the occurrence of the enthalpy-entropy compensation phenomenon, namely related to the desolvation and to the conformational changes in the interaction site. for the interaction study between BSA and ENRO, fluorescence spectroscopy was used, based on ENRO's ability to emit fluorescence. In the study verified that the mechanism of extinction of the fluorescence was static, occurring the formation of BSA-ENRO complex. ENRO demonstrated to bind preferentially to the subdomain IIA (site I) of the BSA, the interaction process being exothermic. the complex has been shown to be more stable at low temperatures. It was also verified that in the process of formation of the BSA-ENRO complex there was the enthalpy-entropic compensation and the formed complex (BSA-ENRO) presented greater capacity of transference of energy to the potential forms than the free molecules, unlike which was observed for bLF and CUR. This study contributes to the knowledge, at the molecular level, of the interaction between milk proteins and molecules of interest in the food area under different temperature conditions and physiological pH, being a useful guide for the optimization of the use of whey proteins as carriers.